Analisis Penayangan Film Kartun Anak-Anak di Televisi Swasta Nasional Indonesia dalam Memberikan Pesan Moral pada Anak-Anak - Elisabeth Nugrahaeni (Communicology: Jurnal Ilmu Komunikasi, 2013)
Abstract This study describes the analysis of a cartoon showing children in national private television in providing moral knowledge. The research was conducted in three private television is RCTI, MNCTV, and SpacetoonTV. The research looked at the moral messages given through these cartoons. Most of television is already presenting cartoon movies that give a moral message. However, the results of this study indicate that Indonesia has not been presented on national television films in the country that gives a moral message in accordance with national culture. Keywords: communication education, cartoon kids, the moral message